MODAL SOSIAL DALAM PRAKTIK KULAKAN MAKANAN TRADISIONAL PASAR NUSUKAN, SURAKARTA - Vyan - Abigel; Danang Purwanto (Jurnal Ilmiah Sosiologi Agama (JISA), 2026)
The traditional food wholesale practice at the three-way intersection of Pasar Nusukan takes place in the early morning in an open area outside the formal market and operates without official supervision. Despite this condition, the activity remains orderly and consistent. This article aims to explain how the elements of social capital networks, norms, and trust work in producing and maintaining order in the wholesale practice of traditional food among informal traders. This study employs a descriptive qualitative approach through field observation, in-depth interviews, and supporting documentation. Informants were selected purposively and included a traders’ coordinator, wholesale sellers, and buyers involved in the wholesale activity. The data were analyzed by grouping the findings into relevant subthemes and interpreting them through Putnam’s three elements of social capital. The findings show that early-morning wholesale activity follows a recurring transaction pattern, and its orderliness is supported by networks built through routine encounters and communication, norms governing payment compliance, product conformity, spatial use, and the acceptance of leftover goods, as well as trust that accelerates transactions while operating unevenly between long-term and new actors. This study shows that Putnam’s social capital theory is relevant not only for explaining order in urban informal economic practices, but also for understanding how risk-sharing and uneven trust produce informal boundaries of membership among market actors.